2020
DOI: 10.18332/tid/116970
|View full text |Cite
|
Sign up to set email alerts
|

The methodology for assessing smoking-attributed mortality based on All Causes of Death Surveillance in Tianjin, China, 2010–2015

Abstract: INTRODUCTION The All Causes of Death Surveillance (ACDS) system was used to measure smoking-attributed mortality by inserting questions on smoking on death certificates. Smoking status information of the deceased has been routinely collected in death certificates since 2010. We describe a death registry-based case-control study using smoking and cause-of-death data for the period 2010-15. METHODS From 2010, three questions about the smoking status of the deceased were inserted in a revised death certificate: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The death registration system in Tianjin is the first and only death registration system which is collecting the smoking information of the deceased in China. Starting at the end of 2009, the current research group has been collecting information routinely on smokers including: smoking status (current smoking, quit smoking, never smoked); cigarettes/day; and years of smoking recorded on the death certificate 10 , 11 . In 2015, in order to further improve the collection of data, smoking information about the duration of smoking cessation was added (if the deceased had quit, the duration of smoking abstinence in years).…”
Section: Introductionmentioning
confidence: 99%
“…The death registration system in Tianjin is the first and only death registration system which is collecting the smoking information of the deceased in China. Starting at the end of 2009, the current research group has been collecting information routinely on smokers including: smoking status (current smoking, quit smoking, never smoked); cigarettes/day; and years of smoking recorded on the death certificate 10 , 11 . In 2015, in order to further improve the collection of data, smoking information about the duration of smoking cessation was added (if the deceased had quit, the duration of smoking abstinence in years).…”
Section: Introductionmentioning
confidence: 99%
“…The death data of CVDs in 2015 were derived from the Tianjin All Cause of Death Surveillance System based on the ICD code of diseased, which covered the registered residence population of the city since 1984 18,19 …”
Section: Methodsmentioning
confidence: 99%
“…The death data of CVDs in 2015 were derived from the Tianjin All Cause of Death Surveillance System based on the ICD code of diseased, which covered the registered residence population of the city since 1984. 18 , 19 Previous studies showed that the health outcomes of CVDs related to elevated SBP included ischemic heart disease (ICD‐10:I20‐I25), rheumatic heart disease (I01, I02.0, I05‐I09), aortic aneurysm (I71), endocarditis, myocarditis and myocardial disease (I33, I40, I42), atrial fibrillation and peripheral neuropathy and other circulatory diseases (I48, I73, I70.2, I00, I02.9, I27‐I28, I30‐I32, I34‐I39, I47, I70.8, I72, I77‐I80, I82‐I84, I86‐ I98, G45), ischemic stroke (I63), and hemorrhagic stroke (I61). The relative risk (RR) per 10 mm Hg increase in SBP by age groups (aged 25 and over) and both sex for each health outcome was showed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%